International multidisciplinary expert panel consensus on breast reconstruction and radiotherapy. Issue 10 (18th July 2019) - Nava, M. B.; Benson, J. R.; Audretsch, W.; Blondeel, P.; Catanuto, G.; Clemens, M. W.; Cordeiro, P. G.; De Vita, R.; Hammond, D. C.; Jassem, J.; Lozza, L.; Orecchia, R.; et al.
Abstract : Background: Conflicting evidence challenges clinical decision‐making when breast reconstruction is considered in the context of radiotherapy. Current literature was evaluated and key statements on topical issues were generated and discussed by an expert panel at the International Oncoplastic Breast Surgery Meeting in Milan 2017. Methods: Studies on radiotherapy and breast reconstruction (1985 to September 2017) were screened using MEDLINE, Embase and CENTRAL. The literature review yielded 30 controversial key questions. A set of key statements was derived and the highest levels of clinical evidence (LoE) for each of these were summarized. Nineteen panellists convened for dedicated discussions at the International Oncoplastic Breast Surgery Meeting to express agreement, disagreement or abstention for the generated key statements. Results: The literature review identified 1522 peer‐reviewed publications. A list of 22 key statements was produced, with the highest LoE recorded for each statement. These ranged from II to IV, with most statements (11 of 22, 50 per cent) supported by LoE III. There was full consensus for nine (41 per cent) of the 22 key statements, and more than 75 per cent agreement was reached for half (11 of 22). Conclusion: Poor evidence exists on which to base patient‐informed consent. Low‐quality studies are conflicting with wide‐ranging treatment options, precluding expert consensus regarding optimal type and timing of breast reconstruction in the context of radiotherapy. There is a need for high‐quality evidence from prospective registries and randomized trials in this field. Abstract : Conflicting evidence challenges clinical decision‐making when breast reconstruction is considered in the context of radiotherapy. This study aimed to evaluate the current literature and generate key statements on topical issues that were discussed by an expert panel at the International Oncoplastic Breast Surgery Meeting in Milan in 2017. Poor evidence exists on which to base patient‐informed consent. Low‐quality studies are conflicting with wide‐ranging treatment options, precluding expert consensus regarding optimal type and timing for breast reconstruction in the context of radiotherapy. There is a need for high‐quality evidence from prospective registries and randomized trials in this field. More research needed urgently Abstract : Antecedentes: El hecho de que la evidencia disponible sea conflictiva supone un reto para la toma de decisiones a la hora de considerar la reconstrucción mamaria en el contexto de radioterapia ( radiotherapy, RT). En el seno de un panel de expertos reunidos durante el International Oncoplastic Breast Surgery Meeting celebrado en Milán en 2017, se revisó la literatura disponible y se generaron y discutieron los aspectos más relevantes. Métodos: Se hizo una búsqueda bibliográfica de los estudios de RT y reconstrucción mamaria (1985‐septiembre de 2017) en las bases MEDLINE, EMBASE y CENTRAL. La revisión de la literatura permitió identificar 30 cuestiones clave controvertidas. A partir de ellas, se construyeron una serie de afirmaciones, para las que se obtuvo el mayor nivel de evidencia ( levels of clinical evidence, LoE) posible. El acuerdo, desacuerdo o abstención respecto a las cuestiones propuestas fueron el resultado de las discusiones de 19 expertos reunidos durante el International Oncoplastic Breast Surgery Meeting . Resultados: Se identificaron 1.522 artículos publicados en revistas con peer review . Se elaboró una lista de 22 afirmaciones clave y se anotó el LoE más alto obtenido para cada una de ellas. El grado de variabilidad fue de II a IV, pero la mayoría de las afirmaciones (54, 5%) obtuvieron un LoE III. Hubo un consenso total en el 41% (9/22) de las afirmaciones, mientras que se obtuvo más de un 75% de acuerdo en la mitad de las afirmaciones (11/22). Conclusión: La evidencia en la que basar el consentimiento informado en estos pacientes es escasa. Se trata de estudios de baja calidad con gran variedad de opciones terapéuticas, que dificultan el consenso de los expertos acerca del tipo y momento óptimo para la reconstrucción mamaria en el contexto de RT. Para obtener datos de mayor calidad se precisan estudios prospectivos y ensayos clínicos en este campo.